SIR SYED AHMED KHAN: ILLUMINATING PATHWAYS TO PROGRESSIVE POLITICS AND SOCIETAL ENLIGHTENMENT FOR MUSLIMS IN UNITED INDIA - Arshad Ali; Zulqarnain Haider; Muhammad Anwar ul Haq; Wajid Aziz Qureshi (International Journal of Contemporary Issues in Social Sciences, 2024)
The Muslims of undivided India from all sphere of life suffered a lot at the hands of British, However, politically they endured severe setbacks after the upheaval of war of independence in 1857. In the light these circumstances, Sir Syed Aḥmad Khan emerged as a staunch Muslim Nationalist and progressive Political thinker. He strived hard to rescue the Muslims from ultimate downfall. In the trek of upliftment of Muslims, he went on ratiocinative about the causes behind the Political decay and ruination the problem and its remedy. Soon, he reached to the conclusion “The main cause of Muslim political decay is ignorance and the only remedy is education”. The Nationalistic and Progressive political thought of Sir Syed Aḥmad Khan can be divided into two phases earlier and later political phases. This research paper has attempted to examine Sir Syed's nationalistic and progressive political ideas and its significance for Muslims in India, which makes him to affirm his survival during the time of colonial forces. Furthermore,Qualitative method of study has been used to carry out this research to its final edge.